2019
DOI: 10.1021/acs.inorgchem.9b00193
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonal to Monoclinic Crystalline Phases Change of BiVO4 via Microwave-Hydrothermal Reaction: In Correlation with Visible-Light-Driven Photocatalytic Performance

Abstract: Explicit control of the crystalline phases and morphology of semiconducting BiVO4 crystals has been successfully synthesized via microwave-hydrothermal condition (MW-HT) without requiring any template/surfactant, doping of metal ions, and altering pH of reaction solution. Unambiguously, the crystalline phase of BiVO4 crystal has transformed from tetragonal zircon type (tz) to monoclinic scheelite (m) via mixed-phase (m-tz) by altering microwave-irradiation time at fixed microwave-irradiation power (800 W) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 68 publications
6
74
0
2
Order By: Relevance
“…The conduction and valence band potentials of a semiconductor can be determined by following eqn (2) and (3): 21,24 E VB ¼ X À E e + 0.5E g (2)…”
Section: Uv-vis Diffuse Reectance Spectroscopy (Drs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The conduction and valence band potentials of a semiconductor can be determined by following eqn (2) and (3): 21,24 E VB ¼ X À E e + 0.5E g (2)…”
Section: Uv-vis Diffuse Reectance Spectroscopy (Drs)mentioning
confidence: 99%
“…Recently, it has been reported that BiVO 4 can be successfully synthesized by a high-pressure microwave method. 24,25 The microwave-assisted synthesis of BiVO 4 under a high pressure can save reaction time and control morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The factor pH is one of the crucial parameters that play a pivotal role in the synthesis of nanoparticles due to the surface charge properties of the photocatalyst. From recent reports [26][27][28], it was observed that the synthesis of BiVO 4 in acidic medium results in the formation of mixed phases (tetragonal and monoclinic). The pH from acidic to basic favors crystallization of BiVO 4 in monoclinic structure and hence in this work it was aimed to study the structural, optical and photocatalytic behavior of BiVO 4 synthesized in basic medium.…”
Section: Introductionmentioning
confidence: 99%
“…The main merits of microwave-assisted chemistry (MWAC) over conventional heating methods include homogeneous heating, fast nucleation processes, good reproducibility, simple control of the reaction parameters, possibility to use non toxic organic solvents and last but not least, it provides a scale-up platform for applications in the industry [15][16][17]. TiO 2 nanostructures synthesized by MWAC have been reported in the past [18][19][20] and recently the work was intensified [16,[21][22][23][24][25][26][27][28][29]. Preparation of P-doped nanostructures of Fe 2 O 3 -TiO 2 mixed oxides [21], selective oxidation of TiO 2 nanoestructures [22], noble-metal free co-catalysts decorating inorganic-organic hybrid materials [16], controlled morphologies and phases of BiVO 4 [27], CdS NRs-carbon NTs for the H 2 production [28] and synthesis of Au/SnS 2 nanoflowers [29] are current examples of the efficient use of MWAC for preparation of several new nanostructures.…”
Section: Introductionmentioning
confidence: 99%